Identification of Public Relation strategies used by the Peruvian Government in the management of social conflicts related to the mining activity in Cajamarca, Peru - Solórzano Castro, Marita (2013)
It is known that mining activity is synonym of investment, growing and development, however many times it becomes cause of controversies, difficulties and unrest; not only between the mining enterprise and the impacted communities but also the government gets involved in the conflicts. This happens, because as the actor in charge of regulate mining activities, it has the obligation of assume a position and to decide about the course of these conflicts.